Factors related to tissue complications resulting from insulin therapy: a cross-sectional study* - Santos, Wallison Pereira dos; Sousa, Mailson Marques de; Gouveia, Bernadete de Lourdes André; Soares, Maria Júlia Guimarães; Almeida, Ana Maria de; Oliveira, Simone Helena dos Santos (Revista da Escola de Enfermagem da USP, 2022)
Objective: To identify factors related to tissue complications resulting from insulin therapy. Method: This is a descriptive, cross-sectional study carried out in a capital of northeastern Brazil. A semi-structured form and an observation guide were applied to assess the performance of insulin preparation and administration techniques. Descriptive statistics, association test, and multivariate logistic regression were used for data analysis. Results: Most participants were female (74.2%), aged between 51 and 70 years (50.0%), and had nine to eleven years of education (36.7%). The presence of some type of local complication in 73.5% of the participants and the failure to rotate the injection sites in 82.3% are highlighted. Being single/widowed and not rotating insulin application sites were related to local complications and increased the chances of their occurrence by 3.51 and 6.70 times, respectively. Conclusion: Marital status and nonrotation of injection site were related to the increased chances of tissue complications resulting from insulin therapy.